Interactions Between Glycogen Synthase Kinase-3β Gene Polymorphisms, Negative Life Events, and Susceptibility to Major Depressive Disorder in a Chinese Population - Yang, Jiarun; Ke, Siyuan; Qiao, Zhengxue; Yang, Xiuxian; Qiu, Xiaohui; Song, Xuejia; Zhao, Erying; Zhou, Jiawei; Zhao, Mingzhe; Yang, Yanjie; Fang, Deyu; Cao, Depin (Frontiers in Psychiatry, 2021)
Background: Recent studies suggest that glycogen synthase kinase (GSK)-3β is involved in the development of major depressive disorder (MDD). The aim of this study was to investigate the interaction between GSK-3β polymorphism (rs6438552, rs334558, and rs2199503) and negative life events in the pathogenesis of major depressive disorder (MDD).Methods: DNA genotyping was performed on peripheral blood leukocytes in 550 patients with MDD and 552 age-and gender-matched controls. The frequency and severity of negative life events were assessed by the Life Events Scale (LES). A chi-square method was employed to assess the gene-environment interaction (G×E).Results: Differences in rs6438552, rs334558, and rs2199503 genotype distributions were observed between MDD patients and controls. Significant G×E interactions between allelic variation of rs6438552, rs334558, and rs2199503 and negative life events were observed. Individuals with negative life events and carrying genotypes of Conclusions: These results indicate that interactions between the GSK-3β rs6438552, rs334558, and rs2199503 polymorphisms and environment increases the risk of developing MDD.